Comprehensive Simulation Curriculum of Transfusion Medicine - Mojca Remskar Konia; Benjamin Rioux-Masse (Association of American Medical Colleges, 2012)
Abstract Introduction This resource is a comprehensive curriculum of transfusion medicine with emphasis on acute hemolytic transfusion medicine and massive transfusion protocol. It includes scenarios located in various hospital settings (i.e., ward, operating room, ICU) to allow for training of variety of learners. The simulation scenario, suggested reading, PowerPoint presentations and test allow for learners to gain transfusion medicine knowledge, skills, and attitudes crucial for anyone who uses blood products in their health care practice. Methods The included material presents four simulation scenarios, which allow participants to manage a massively bleeding patient and/or a patient with acute hemolytic transfusion reaction in different clinical environments. The scenarios are based on the following clinical situations: (1) an obstetric patient undergoing cesarean section complicated with a massive bleeding in the operating room, (2) a postsurgery patient who underwent liver transplant with massive bleeding from drains in the ICU, (3) a floor patient with massive gastrointestinal bleeding, and (4) an acute hemolytic transfusion reaction scenario in an awake patient on the floor. Results At our institution we have utilized the transfusion curriculum for 1 year in education of medical students, anesthesiology residents, and surgery residents. We had 95 learners participate in this educational activity. On a scale from 0 to 5 (5 being exceptional, 1 being unsatisfactory) average learner satisfaction was rated as 4.43 +/− 0.5 (range 3 to 5). Learner knowledge increased from pretest to posttest with pretest scores averaging 39% and posttests averaging 77.5%. Knowledge was also retained 6 weeks later at 82% correctly answered questions. Discussion The authors feel strongly that this educational curriculum is an excellent educational tool. Through the design process we have learned about interdisciplinary development of curriculums, learner satisfaction, educational effectiveness of the curriculum, and learner gaps that need attention.